CGIAR Genebank Platform: Evaluation Report - Humphrey, S.; Coombs, D.; Pritchard, H.; Pham, J.L.; Sellitti, S.; Anand, S. (CGIAR Independent Advisory and Evaluation Service, 2024)
The purpose of the 2023 evaluation of the Genebank Platform was to support the institutional learning of Crop Trust and CGIAR and provide evidence regarding the efficiency and effectiveness of the Genebank Platform (from 2017-21). The evaluation exercise aimed to also identify good practices and lessons for the Genebanks Initiative and Genetic Innovation Science Group and CGIAR at large.